IMPLEMENTATION OF TECHNOLOGICAL INNOVATION IN BUSINESS OPERATIONS MANAGEMENT OF START-UP COMPANIES IN THE E-COMMERCE SECTOR - Billy Martasandy (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Research purposes This study focuses on the implementation of innovation technology in the management of operational business start-up companies in the e- commerce sector. The method used is qualitative, with a study field. As for the participants in the study, they are two employees of a start-up company in the e- commerce sector. Research result This implementation of innovation technology in management operational business, especially in the context of start-up companies in the e-commerce sector, has significant implications. Implementation of innovation technology has facilitated process automation, management of inventory efficiency, and optimization of chain supply, all of which have a positive impact on improving company performance and productivity. Study This confirms the importance of integrating technology into the management of operational start-up companies in the e-commerce sector. Temporary challenge in implementation: No can be neglected. Benefits period length: to increase efficiency and experience, customers make investment in technology an important step. For growth and success, company length.